(untitled) (Global Journal of Science Frontier Research, 2011)
Food supply can be induced either by increase in production or reduction in loss. Many post harvest losses are direct result of factors such as high field temperatures on crops before harvesting, pests and diseases attack etc, hence increase in the losses after harvest. The study area is Imeko Afon Local Government Area of Ogun State. Purposive sampling technique was employed in selecting 88 respondents and administering the questionnaire, and 88 were used for analyzing the data. Results on socio-economic characteristics revealed that, majority of the farmers (69%) fell into the active workforce and they had farm sizes ranging from 1-5hectares. Larger percentage of the farmers had an education below secondary level (83%).Majority of the tomato farmers had household size greater than 33% and 68% of the farmers had less than 16 years experience in tomato production. About 72% make use of van/pick up in transporting their produce from the farm to the market. No storage facilities were used in the study area to preserve the fruits from rotten after harvesting as at the time of study. The average gross margin with post harvest losses (9,251.41) is less than the average gross margin when no damage occurred in the fruits (72,752.55), thus showing that post harvest losses reduce the mine of farmers in the study area. All the independent variables tested on the dependent variable (Quantity of fruit loss) tested were significant at 5%. The effects of post harvest losses in the study area leads to wastage of the products and tend to frustrate the efforts put into production and their income on the produce.